SAP-expressing T peripheral helper cells identify systemic lupus erythematosus patients with lupus nephritis - Gartshteyn, Yevgeniya; Geraldino-Pardilla, Laura; Khalili, Leila; Bukhari, Shoiab; Lerrer, Shalom; Winchester, Robert J.; Askanase, Anca D.; Mor, Adam (Frontiers in Immunology, 2024)
Introduction: T follicular (TFH) and peripheral helper (TPH) cells have been increasingly recognized as a pathogenic subset of CD4 T cells in systemic lupus erythematosus (SLE). The SLAM Associated Protein (SAP) regulates TFH and TPH function by binding to the co-stimulatory signaling lymphocyte activation molecule family (SLAMF) receptors that mediate T cell -B cell interactions. SAP and SLAMF are critical for TPH-dependent B cell maturation into autoantibody-producing plasma cells that characterize SLE pathogenesis. We hypothesized that SAP-expressing TPH cells are involved in the pathogenesis of lupus nephritis (LN). Methods: Peripheral blood mononuclear cells (PBMC) were isolated and stained for cell surface markers, followed by permeabilization and staining of intracellular SAP for spectral flow cytometry analysis. We also analyzed SAP expression from renal infiltrating LN T cells using the available single-cell RNA sequencing (scRNA seq) Accelerated Medicines Partnership (AMP) SLE dataset. Results: PBMC from 30 patients with SLE (34±10 years old, 83% female), including 10 patients with LN, were analyzed. We found an increase in total SAP-positive CD4 and CD8 T cells in SLE compared with controls (55.5±2.6 vs. 41.3±3.4, p=0.007, and 52.5±3.0 vs. 39.2±2.8, p=0.007 respectively). In CD4 T cells, the highest SAP expression was in the TPH subset. The frequency of SAP + TPH in circulation correlated with disease activity; SLE patients with renal disease had higher levels of circulating SAP + TPH that remained significant after adjusting for age, sex, race, low complements, and elevated anti-dsDNA (p=0.014). scRNA-seq data of renal infiltrating T cells in LN identified SAP expression to localize to the TFH-like CD4 cluster and GZMK+ CD8 cluster. Increased SAP expression in LN was associated with the differential expression of SLAMF3 and SLAMF7 and granzyme K and EOMES. The existence of two predominant SAP expressing subsets, the TFH-like CD4 and GZMK+ effector CD8 T cells, was verified using scRNAseq data from a human transcriptomic atlas of fifteen major organs. The expansion of SAP-expressing T helper cells was associated with LN in our cohort and verified using scRNA-seq data of renal infiltrating T cells. Improved SLAM and SAP signaling understanding can identify new therapeutic targets in LN.